Scrutinizing the Lecturers’ Spoken Discourse Markers Used in the Virtual Classroom - Alif, Wening Nur Habibah; Rukmini, Dwi; Meylana, Ardhy (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
Abstract. Classroom learning is an active interaction between the lecturer and students. In its implementation, support from both parties is needed to achieve the learning objectives as expected. Discourse Markers (DMs) are tools used by lecturer and students in the classroom to control their conversation so that the core of the conversation is readily accepted. Since Indonesian students belong to EFL learners, using DMs between native and non-native speakers at the school is an exciting discussion to explore. Of course, many distinctions between both may enrich our insight into DMs. The subjects of this research are two lecturers who teach virtually via Zoom; one of the lecturers is a native speaker, and the other one is a non-native speaker. The qualitative descriptive design will be applied in this research. The data are taken from the learning Zoom recording in the English study program and uploaded to the YouTube channel. It will be transcribed into writing, and then the transcripts will be analyzed to find variations and the functions of discourse markers used by lecturers in the classroom. The theory applied in this study is Biber 2007) theory about linking adverbials or DMs. This research's expected result is that the study will show the similarities and differences between DMs used by native and non-native speaker lecturers.